Nguyen Trai of benevolence and righteousness are necessary for Vietnamese today - Pham, Thi Kien (2022)
Nguyen Trai is a man with a great personality in Vietnam. He has morality, culture, pure soul, and profound wisdom of all times. Nguyen Trai lived in the 15th century in a feudal society with many changes. The paper studied Nguyen Trai’s philosophical thoughts to help develop a prosperous and happy country using the nation’s traditional cultural values. The article uses the methodology of dialectical materialism as a general principle and a specific historical principle to evaluate Nguyen Trai’s benevolence and righteousness in terms of compassion, justice, and management, associated with the interests of the people, the community, and society. The article also uses analytical and synthesis methods to highlight the content of benevolence and righteousness in the cultural tradition of the Vietnamese nation today. The Covid-19 pandemic had affected the world in general and Vietnam in particular. So Nguyen Trai’s thought culture is powerfully and effectively prompt in responding to the Covid-19 pandemic in Vietnam and other countries today. In this article, Nguyen Trai’s benevolence and righteousness fairness clearly define the responsibility of the state and the obligation of citizens to promote the traditional cultural values of the nation.